A systematic review of prospective epidemiological research into injury and illness in Olympic combat sport. Issue 1 (27th September 2017) - Bromley, Sally J; Drew, Michael K; Talpey, Scott; McIntosh, Andrew S; Finch, Caroline F
Abstract : Background: Combat sports involve body contact through striking, kicking and/or throwing. They are anecdotally referred to as 'dangerous', yet long-term investigation into specific injury rates is yet to be explored. Objective: To describe incidence and prevalence of injury and illness within Olympic combat sports and to investigate risk of bias of prospective injury and illness research within these sports. Methods: We systematically searched literature published up until May 2016. We included prospective studies of injury/illness in elite combat athletes lasting more than 12 weeks. Risk of bias was assessed using a modified version of the Downs and Black checklist for methodological quality. Included studies were mapped to the Oxford Centre for Evidence-Based Medicine levels of evidence. Results: Nine studies were included, and most (n=6) had moderate risk of bias. Studies provided level 1/2b evidence that the most frequently injured areas were the head/face (45.8%), wrist (12.0%) and lower back (7.8%) in boxing; the lower back (10.9%), shoulder (10.2%) and knee (9.7%) in judo; the fingers (22.8%) and thigh (9.1%) in taekwondo; and the knee (24.8%), shoulder (17.8%) and head/face (16.6%) in wrestling. Heterogeneity of injury severity classifications and inconsistencies inexposure measures prevented any direct comparisons of injury severity/incidence across combat sports. Conclusions: There is currently a lack of consensus in the collection of injury/illness data, limiting the development of prevention programmes for combat sport as a whole. However, sport-specific data that identify body areas with high injury frequency can provide direction to clinicians, enabling them to focus their attention on developing pathologies in these areas. In doing so, clinicians can enhance the practical elements of their role within the integrated combat sport performance team and assist in the regular update of surveillance records.